2020
DOI: 10.1002/jsfa.10245
|View full text |Cite
|
Sign up to set email alerts
|

Variation in flavonoids in a collection of peppers (Capsicum sp.) under organic and conventional cultivation: effect of the genotype, ripening stage, and growing system

Abstract: BACKGROUND In recent years, the acreage used for organic agriculture and the demand for organic fruit and vegetables have increased considerably. Given this scenario, landraces, such as Capsicum landraces, can provide valuable germplasm. Capsicum peppers are very interesting because of their high phenolic content, and particularly their flavonoid content, which provides a high added value. Moreover, the broad genetic diversity in local varieties expands the opportunities for adaptation to organic production an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…From a redox viewpoint, it has been found that reactive oxygen species (ROS) metabolism is also affected during fruit ripening, leading to major changes in total soluble reducing equivalents and the antioxidant capacity in fruits [41]. The profile of the major non-enzymatic antioxidants, including ascorbate, glutathione, carotenoids and polyphenols, has been followed during ripening in pepper fruits [4,11,12,[42][43][44][45][46], but less is known on how enzymatic antioxidants evolve with this physiological process. These enzyme systems basically include superoxide dismutase (SOD), catalase (CAT) and the ascorbate-glutathione cycle as the primary defense barriers against ROS, and some NADP-dehydrogenases as a secondary system to help the antioxidative enzymatic block.…”
Section: Introductionmentioning
confidence: 99%
“…From a redox viewpoint, it has been found that reactive oxygen species (ROS) metabolism is also affected during fruit ripening, leading to major changes in total soluble reducing equivalents and the antioxidant capacity in fruits [41]. The profile of the major non-enzymatic antioxidants, including ascorbate, glutathione, carotenoids and polyphenols, has been followed during ripening in pepper fruits [4,11,12,[42][43][44][45][46], but less is known on how enzymatic antioxidants evolve with this physiological process. These enzyme systems basically include superoxide dismutase (SOD), catalase (CAT) and the ascorbate-glutathione cycle as the primary defense barriers against ROS, and some NADP-dehydrogenases as a secondary system to help the antioxidative enzymatic block.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, during ripening, NO content and catalase activity lower [43]. The content of the main non-enzymatic antioxidants (ascorbate, glutathione, carotenoids and polyphenols) has also been investigated in pepper fruit ripening [7,8,28,[44][45][46][47][48][49]. NO treatment was shown to prevent some of the changes undergone by these parameters, thus confirming the delaying effect of the ripening process indicated above [38,50,51].…”
Section: Introductionmentioning
confidence: 61%
“…Quercetin and derivatives have been already identified in fruits from diverse pepper varieties [8,[61][62][63][64]. However, there is still very little data on the quercetin profile and its role throughout the ripening process in pepper fruits [28,65], and nothing is known about its modulation by NO. This work is the first report of the regulatory events which shape the quercetin content in fruits from a higher plant.…”
Section: Quercetinmentioning
confidence: 99%
“…This group includes flavonoids such as isoflavones, anthocyanidins, chalcones, and anthocyanins. In general, flavonoids have antibacterial, antifungal, antioxidant, and anticancer effects [ 1 , 8 , 13 , 28 ].…”
Section: Introductionmentioning
confidence: 99%